Tell me where it hurts, an' I'll tell you who to call: industrialized countries' agricultural policies and developing countries - Diao, Xinshen; Díaz-Bonilla, Eugenio; Robinson, Sherman; Orden, David (International Food Policy Research Institute, 2005)
This paper accomplishes two objectives. First, it provides simulation results from a computable general equilibrium (CGE) model that have helped focus the debate about the potential effects of agricultural trade liberalization on developing countries. The aggregate numbers show modest net positive effects over a medium-term period (five years out). First, when developed countries fully remove their subsidies and trade barriers, welfare and GDP of the developing countries rise, as do value added in agricultural production and agro-industries, and agricultural exports. Focal point estimates that we provide are increases in welfare and GDP of $10 billion and $15 billion, respectively, while agricultural value added increases $23 billion and agricultural exports by $37 billion. Second, when developing countries also eliminate their subsidies and trade barriers, there is an additional net gain in aggregated developing country welfare and GDP—which now increase by nearly $20 billion and $38 billion. Thus, developing countries gain from developed country liberalization, but there are also gains from reform of their own policies. Our results suggest a fairly even balance between these sources of gains. The second and equally important contribution of the paper is to describe the heterogeneity among developing countries in terms of their agricultural resources, and to disaggregate the simulated results among 40 developing countries or regions. The basic model includes the innovation of assuming there is unemployed labor in developing countries, so growth in agricultural production has a modest “multiplier” effect. The basic model also allows for a slight positive effect of increased trade on productivity—the focal results cited above include this impact. Effects are distinguished between elimination of subsidies and trade barriers by the US, the EU, Japan and Korea, and all developed countries simultaneously. Effects on different developing countries and regions differ due to differences in the subsidy and trade barrier instruments utilized by the developed countries, the commodities affected, and the trade patterns and volumes evident in the initial baseline data.